BRANDING AND IMAGE AS SIGNIFICANT FACTORS FORMING THE URBANONYMIC SPACE OF ALMATY (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The formation of urban space is a multifaceted phenomenon. Although architecture plays an important role in the formation of a city, what it is called becomes even more important. Therefore, in the theory of architecture, the architect gets the opportunity to work with the environment, and not with a specific object. The object in the material space in which the architect works forms a common urban space. It can be variously called  a particle of the city ,  urbanonymic space ,  a particle of urban space ,  urban landscape,  urban interior ,   urban landscape.The structure of the onomasticon of the city of Almaty, historical changes reflected by actual data, names of objects forming the image of the city are studied. Many cultural and ethnic objects that have become personal brands develop tourism in the region. And its name is a factor influencing the formation of the brand. The image of the city of Almaty combines modern business centers and Soviet postmodernism, which is reflected in the onomasticon of the city. We see that the impact of the consequences of global globalization on the names of the objects of the city of Almaty also prevails. Its advantages and disadvantages will also be discussed. An onomastic analysis was also made about the names of objects of the last period that became the brand of the city of Almaty. The article is devoted to the review of the names of objects that form the urbanonymic space of the city of Almaty, the analysis of the reasons underlying the creation of the brand and image factors.